2009
DOI: 10.1111/j.1528-1167.2009.02219.x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the pathophysiology of psychomotor regression in CSWS syndromes from FDG‐PET and EEG‐fMRI

Abstract: SUMMARYEpilepsy syndromes with continuous spikes-andwaves during slow sleep (CSWS) are age-related epileptic encephalopathies characterized by the development of various types of psychomotor regression in close temporal concordance with the appearance of the electroencephalography (EEG) pattern of CSWS. Functional cerebral imaging studies performed in children with CSWS have shown evidence for the existence of increase in metabolism or perfusion at the site of the epileptic focus, associated with decrease in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 15 publications
1
16
1
Order By: Relevance
“…suggested, basing on functional cerebral imaging studies, cognitive impairment in children with CSWS may also be related to neurophysiological changes in far brain areas connected with the site of EEG foci. [14] We suggest that serial neuropsychological assessments should be performed, during the follow-up, in patients with early-onset hydrocephalus and CSWS to test and verify the cognitive and behavioral pattern that we found in our case.…”
Section: Discussionsupporting
confidence: 52%
“…suggested, basing on functional cerebral imaging studies, cognitive impairment in children with CSWS may also be related to neurophysiological changes in far brain areas connected with the site of EEG foci. [14] We suggest that serial neuropsychological assessments should be performed, during the follow-up, in patients with early-onset hydrocephalus and CSWS to test and verify the cognitive and behavioral pattern that we found in our case.…”
Section: Discussionsupporting
confidence: 52%
“…Based on young adults as controls, the results are not univocal. De Tiege et al did succeed detecting areas of remote inhibition in children aged 5 to 11 years with a particular epileptic encephalopathy and to see them vanish when epilepsy and cognitive deficits recover [24,39,40]. Some authors showed a high SPM performance (86%) for correct localization of the seizure onset zone in adolescents (12 to 15 years) [26], but others achieved a rate of only 13% in children from the age of 3 [14].…”
Section: Discussionmentioning
confidence: 99%
“…They usually extend beyond the epileptic focus and may involve distant areas connected to it (25,30). An EEG-functional MRI approach proved that such widespread hypometabolism resulted from both surrounding and remote inhibition, which might sustain the neuropsychologic impairment (34,35).…”
Section: F-fdg Pet and Detection Of Hypometabolic Areas In Epileptic mentioning
confidence: 99%